Requirements for symmetric block encryption algorithms developed for software and hardware implementation (Journal of Mathematics Mechanics and Computer Science, 2021)
The hardware and software cryptographic information protection facility is one of the most important components of comprehensive information security in information and communication systems and computer networks. This article outlines and systematizes the basic requirements for modern cryptographic information protection facilities (CIPFs), and describes the stages of developing a symmetric block encryption algorithm. Based on the basic requirements for CIPFs, criteria for evaluating the developed cryptographic encryption algorithms were determined. The possibilities and necessary limitations of the types of cryptographic transformations (primitives) in the software and hardware implementation of the developed symmetric block encryption algorithm are considered and defined. On the basis of the developed encryption algorithm, SDTB Granit plans to implement a model of a hardware-software complex for off-line (linear) data encryption, taking into account all the listed requirements and characteristics.The article presents a new version of the "AL01" encryption algorithm, which is guided by the basic requirements for creating symmetric block ciphers.
Keywords: symmetric block algorithm; cryptographic information protection facility; software; hardware-software; and hardware implementation of encryption algorithms; cryptographic primitives